The social impact of distance learning in Roman schools: “Success,” social innovation, teaching practices - Lo Presti, Veronica (Frontiers in Sociology, 2023)
Faced with the national emergency linked to the spread of Covid-19 in Italy, digital technologies have made it possible to carry out the ordinary activities of the various educational agencies, through the main tool of Distance Learning (DaD), The intensive use of information and communication technologies (ICT) and the guarantee of accessibility represent an enabling prerogative for current education systems, enriching training in a variety of ways and opportunities which must be accessible to all (EU, 2018). ICTs take on a propulsive function for change in schools because they make it possible to affect the school setting, to transform the learning environment by redesigning space, reorganizing time, modifying communication and socialization processes (Calvani, 2007), encouraging, in students, the development of key competencies in digital literacy and media education (Lo Presti, 2019). Considering the context of a school transformed and renewed by the teaching and training potential of ICT, it becomes central to reconstruct the requests and needs developed by the practitioners of educational policies to cope with the reorganization of teaching methods and times at the time of DaD. Starting from these premises, the paper focuses attention on the social impact (OEC-DAC in Stern, 2016) of DaD to evaluate: the extent and intensity of the methodological-didactic innovation required of teachers for the organization and conduction of remote lessons; the increase - in students - of transversal and digital literacy skills (team working, problem solving, etc) potentially associated with the use of ICTs; the involvement and collaboration of families in the process of assessing and verifying learning. The reflection is part of a broader research project by Sapienza University of Rome entitled "The Social Impact Assessment of DaD after Covid-19”; a three-year evaluation research that aimed to identify - from the DaD experience - indications useful in re-designing the school’s intervention strategy in the phases following the pandemic; for this reason it adopted an analysis perspective that valorized the positive and most successful aspects (Stame, Lo Presti, 2015) in the testimonies of the teachers and students involved in the first phase of the research (conducted in May-June 2021).